Hot water extract of Chlorella vulgaris induced DNA damage and apoptosis - Yasmin Anum, Mohd Yusof (Hospital Clinicas, Univ Sao Paulo, 2015)
OBJECTIVES: The aim of this study was to determine the antiproliferative and apoptotic effects of hot water extracts of Chlorella vulgaris on hepatoma cell line HepG2. INTRODUCTION: The search for food and spices that can induce apoptosis in cancer cells has been a major study interest in the last decade. Chlorella vulgaris, a unicellular green algae, has been reported to have antioxidant and anti-cancer properties. However, its chemopreventive effects in inhibiting the growth of cancer cells have not been studied in great detail. METHODS: HepG2 liver cancer cells and WRL68 normal liver cells were treated with various concentrations (0-4 mg/ml) of hot water extract of C. vulgaris after 24 hours incubation. Apoptosis rate was evaluated by TUNEL assay while DNA damage was assessed by Comet assay. Apoptosis proteins were evaluated by Western blot analysis. RESULTS: Chlorella vulgaris decreased the number of viable HepG2 cells in a dose dependent manner (p < 0.05), with an IC50 of 1.6 mg/ml. DNA damage as measured by Comet assay was increased in HepG2 cells at all concentrations of Chlorella vulgaris tested. Evaluation of apoptosis by TUNEL assay showed that Chlorella vulgaris induced a higher apoptotic rate (70%) in HepG2 cells compared to normal liver cells, WRL68 (15%). Western blot analysis showed increased expression of pro-apoptotic proteins P53, Bax and caspase-3 in the HepG2 cells compared to normal liver cells WRL68, and decreased expression of the anti-apoptotic protein Bcl-2. CONCLUSIONS: Chlorella vulgaris may have anti-cancer effects by inducing apoptosis signaling cascades via an increased expression of P53, Bax and caspase-3 proteins and through a reduction of Bcl-2 protein, which subsequently lead to increased DNA damage and apoptosis.